A Concept for an Emergency Countermeasure against Radioactive Wastewater Generated in Severe Nuclear Accidents Like the Fukushima Daiichi Disaster. (1st February 2016) - Kim, Kwang-Wook; Lee, Keun-Young; Lee, Eil-Hee; Baek, Yeji; Chung, Dong-Yong; Moon, Jei-Kwon
Abstract: This work studied a concept of prompt countermeasure to minimize the accumulation of radioactive wastewater generated in severe nuclear accidents like the Fukushima Daiichi accident. A sequential precipitation process for the removal of Cs, Sr, I, and residual nuclides of Co, Mn, Sb, and Ru was suggested as a way to embody this concept. The process was confirmed to be possible as an effective and rapid emergency treatment for radioactive wastewater using many experiments with non-radioactive and active nuclides. Cobalt ferrocyanide—impregnated chabazite zeolite, Ba-impregnated 4A zeolite, and Ag-impregnated 13X zeolite were chosen as adsorbents for Cs, Sr, and I in this work had very high selectivities and fast adsorption rates with decontamination factors (DFs) on the order of 10 2 to 10 3 . The adsorbent powders were rapidly settled in solution within 5 to 10 min by adding a coagulant of ferric ions. The residual nuclides could be removed by coprecipitation using ferric ion and flocculation using anionic polyacrylamide with DFs of more than 100 within 10 min.